PENGARUH ALIRAN KAS BEBAS TERHADAP KEPUTUSAN PENDANAAN MELALUI SET KESEMPATAN INVESTASI DAN NILAI PEMEGANG SAHAM SEBAGAI MODERASI - Zannati, Rachma; Pratiwi, Wulandhari (Economic Faculty, Attahiriyah Islamic University, 2018)
This study aims to determine the impact of various corporate contextual factors through investment opportunities, earnings management, on the influence of the level of free cash flow on funding decisions. The sample in this study were 18 retail trade companies that were listed on the Indonesia Stock Exchange for 5 years (2013-2017). The analysis technique used is MODPROBE macro v 2.0 using SPSS 22 program. The results of statistical tests in this study indicate that together (Test-F) free cash flow on funding decisions, investment opportunity sets as moderating variables have a significant effect in strengthening flow relationships free cash on funding decisions and shareholder value as moderating variables have a significant effect in strengthening the relationship of free cash flow to funding decisions. Then in the T-Test all variables have a significant effect on funding decisions. Keywords: Free Cash Flow, Investment Opportunity Set, Shareholder Value, Funding Decision